Toward Economic Growth and Value Creation Through Social Entrepreneurship: Modelling the Mediating Role of Innovation - Wang, Wenjie (Frontiers in Psychology, 2022)
The concept of social entrepreneurship emerged as a significant factor that contributes towards public welfare and prosperity. Recent examinations showed that social entrepreneurship influences the economic growth and sustainable of the state. Therefore, the underlying aim of this study was to investigate the impact of social entrepreneurship on sustainable economic growth and value creation. This study also undertook to observe the mediating role of innovation in the relationship between social entrepreneurship and sustainable economic growth and between social entrepreneurship and value creation. A questionnaire technique was adopted to obtain data from 343 tour operators in China. The SmartPLS software was used to analyze the data through the aid of a structural equation modelling (SEM) technique. The results revealed that social entrepreneurship has an effect on sustainable economic growth and value creation. The results also demonstrated that innovation has an effect on sustainable economic growth and value creation. Moreover, it was also observed that innovation mediated the relationship between social entrepreneurship and sustainable economic growth and between social entrepreneurship and value creation. Theoretically, this paper made a valuable contribution by examining the impact of social entrepreneurship on sustainable economic growth and value creation and innovation as a mediator. In terms of practical implications, this paper would certainly aid the policymakers to devise policies and strategies aim to encourage and promote social entrepreneurship. Some limitations of this study were associated with small sample size that included the tour operators in China only. Moreover, future studies can introduce other mediating and moderating variables in order to gain a deeper insight into the phenomenon.